The evolving role of quantitative actigraphy in clinical sleep medicine. (April 2023) - Liguori, Claudio; Mombelli, Samantha; Fernandes, Mariana; Zucconi, Marco; Plazzi, Giuseppe; Ferini-Strambi, Luigi; Logroscino, Giancarlo; Mercuri, Nicola Biagio; Filardi, Marco
Abstract: Actigraphy has a consolidated role in Insomnia and Circadian Rhythm Sleep-Wake Disorders (CRSWD) and recent studies have highlighted the use of actigraphy for narcolepsy and REM sleep behaviour disorder (RBD). This review aims at summarising the results of studies published over the last decade regarding the use of actigraphy. Thirty-five studies proved eligible, and results were analysed separately for insomnia, narcolepsy and RBD. Actigraphy showed to consistently differentiate insomnia patients from healthy controls. Furthermore, the application of advanced analytical techniques has been shown to provide both unique insights into the physiology of insomnia and sleep misperception and to improve the specificity of actigraphy in detecting wakefulness within sleep periods. Regarding narcolepsy, several studies showed that actigraphy can detect peculiar sleep/wake disruption and the effects of pharmacological treatments. Finally, although the number of studies in RBD patients is still limited, the available evidence indicates a reduced amplitude of the activity pattern, sleep-wake rhythm dysregulation and daytime sleepiness. Therefore, the potential use of these markers as predictors of phenoconversion should be further explored. In conclusion, quantitative actigraphy presents a renewed interest when considering the possibility of using actigraphy in clinical sleep medicine to diagnose, monitor, and follow sleep disorders other than CRSWD.